Pengaruh Kepemimpinan, Kepuasan Kerja dan Motivasi Kerja Terhadap Loyalitas Karyawan - Maulidana, Hibban; Hermansyah, Muhammad (MES Bogor, 2024)
Employee loyalty is reflected in employee obedience, responsibility and discipline. Initial observations show that the number of employees is decreasing from year to year, and some employees violate regulations, such as arriving late and not following company regulations. Therefore, the aim of this research is to test whether leadership style, motivation and rewards influence employee retention. The research method used is a quantitative approach, namely analysis of numerical data processed using statistical methods. This research was conducted to determine the influence of leadership, job satisfaction, and motivation on employee loyalty. The sampling technique used saturated samples with a sample size of 13 respondents. The data collection methods used were questionnaires, interviews, documentation and observation. The data analysis technique uses multiple regression analysis using the IBM SPSS 25 program. The conclusion from these results is that the influence of leadership, job satisfaction and motivation has a significant influence on employee loyalty. Suggestions for future researchers are to collect a larger sample in the company and fill out the questionnaire in language that is easier for employees to understand.